Incidence of perioperative acute kidney injury and its outcome in general surgical patients - Hamzah Sukiman (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Acute kidney injury (AKI) is known to complicate surgery in 13% of patients. It is associated with significant morbidity, increased costs and mortality. Surgery is a known risk factor, estimated to cause one-third of all in-hospital AKI. This study aims to determine the incidence of perioperative AKI among patients undergoing surgery and to identify the risk factors and associated adverse outcomes. It is a single-centre, prospective, observational study conducted among general surgical patients between March to September 2018. Adult patients who are admitted for more than 24 hours and who undergo surgery under general or regional anaesthesia are recruited, and those with pre-existing ESRF are excluded. We employed the KDIGO definition of AKI, which is an elevation of serum creatinine by more than 1.5 times baseline. Baseline creatinine level is obtained from previous records or, in its absence, is back-calculated using the MDRD formula, assuming a baseline GFR of 75 ml/min. The incidence of perioperative AKI is 20.2%. Factors that, on bivariate analysis, are associated with AKI include age (p<0.001), presence of diabetes mellitus (p<0.001), hypertension (p<0.001), chronic kidney disease (CKD) (p<0.001), sepsis (p<0.001) and shock (p<0.001). The length and type of surgery (emergency vs. elective) are also associated with AKI (p<0.001, p=0.011). A multivariate analysis using binary logistic regression showed that age (p=0.010), pre-existing CKD (p=0.002) and length of surgery (p=0.010) are independently associated risk factors. AKI is significantly associated with adverse outcomes namely mortality (p<0.001), permanent kidney damage (p<0.001), prolonged length of stay (p<0.001), need for acute dialysis (p<0.001), ICU admission (p<0.001), mechanical ventilation, (p<0.001) and inotropic support (p<0.001). In conclusion, a high proportion of patients undergoing surgery may develop perioperative AKI, which leads to poorer outcomes. Identifying those at risk is crucial to future stratify patients, enabling better prognostication and calculation of drug prescription.